Evaluation of the appropriateness of frozen plasma usage after introduction of prothrombin complex concentrates: a retrospective study. Issue 3 (30th December 2014) - Shih, A. W.; Kolesar, E.; Ning, S.; Manning, N.; Arnold, D. M.; Crowther, M. A.
<x xml:space="preserve">Abstract</x> Background Prothrombin complex concentrates (PCCs) can be used instead of frozen plasma (FP) transfusion to reverse the effect of warfarin. Audits have demonstrated over usage of FP transfusions even before the introduction of PCC. The objective of this study was to determine the appropriateness of current FP transfusion practice in the current era since the introduction of PCCs. Methods A retrospective cohort study of consecutive patients receiving FP over 3 months was carried out. Each episode of FP use over a 24‐h period was adjudicated independently by two reviewers as appropriate (consistent with Canadian/AABB guidelines), appropriate but inconsistent with guidelines or inappropriate. Discrepancies were resolved by a third reviewer. Use of FP to reverse warfarin was considered inappropriate. FP usage from previous years was assessed as baseline. Results During the study period, 111 FP transfusions were administered. 74·8% of FP usage occurred in the ICU. The proportion of FP transfusions that were deemed appropriate, inconsistent yet appropriate or inappropriate were 33/89 (37·1%), 16/89 (18·0%) and 40/89 (44·9%), respectively, when use of FP for therapeutic plasma exchange was excluded. The most common reasons for inappropriate use were the absence of bleeding with an increased INR or warfarin reversal. Conclusion Our study is the first to audit FP transfusions in the post‐PCC era in Canada. FP usage remains inappropriately high in INR prolongation without another indication or to reverse warfarin. Targeted interventions to reduce FP usage in the future should focus on the ICU and on education about warfarin reversal.